2015
DOI: 10.1038/srep14862
|View full text |Cite
|
Sign up to set email alerts
|

Habitat fragmentation is associated to gut microbiota diversity of an endangered primate: implications for conservation

Abstract: The expansion of agriculture is shrinking pristine forest areas worldwide, jeopardizing the persistence of their wild inhabitants. The Udzungwa red colobus monkey (Procolobus gordonorum) is among the most threatened primate species in Africa. Primarily arboreal and highly sensitive to hunting and habitat destruction, they provide a critical model to understanding whether anthropogenic disturbance impacts gut microbiota diversity. We sampled seven social groups inhabiting two forests (disturbed vs. undisturbed)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
227
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(249 citation statements)
references
References 56 publications
15
227
6
1
Order By: Relevance
“…Habitat degradation has impacted the black howler monkey ( Alouatta pigra ) gut microbiome and resulted in the decrease of the alpha diversity of their gut microbiome (Amato et al, ). Other studies have revealed that the gut microbiome of the Udzungwa red colobus monkey ( Procolobus gordonorum ) in the undisturbed forest has significantly higher alpha diversity than that in the disturbed forest (Barelli et al, ). Thus, the evaluation of the relationship between fragmented habitat and gut microbiome diversity will be useful for the effective management of giant pandas.…”
Section: Future Directionsmentioning
confidence: 99%
“…Habitat degradation has impacted the black howler monkey ( Alouatta pigra ) gut microbiome and resulted in the decrease of the alpha diversity of their gut microbiome (Amato et al, ). Other studies have revealed that the gut microbiome of the Udzungwa red colobus monkey ( Procolobus gordonorum ) in the undisturbed forest has significantly higher alpha diversity than that in the disturbed forest (Barelli et al, ). Thus, the evaluation of the relationship between fragmented habitat and gut microbiome diversity will be useful for the effective management of giant pandas.…”
Section: Future Directionsmentioning
confidence: 99%
“…Previous studies have identified host genetics as a crucial determinant of the gut microbiota (Bonder et al, 2016;Kurilshikov, Wijmenga, Fu, & Zhernakova, 2017), which varies not only between species due to differences in the digestive tract characteristics and functions (Ley et al, 2008), but also within species, with genetically similar individuals having greater gut microbial similarities than genetically different individuals (Goodrich et al, 2016(Goodrich et al, , 2014. However, recent studies have indicated that environmental factors play more crucial roles in shaping the gut microbiota than host genetics (Barelli et al, 2015;David et al, 2014;Nelson, Rogers, Carlini, & Brown, 2013;Rothschild et al, 2018;Vangay et al, 2018), with genetically unrelated individuals who live together in the long term having similar gut microbiota and relatives who live apart exhibiting significant differences in their gut microbiota (Rothschild et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, microbiome similarity between kin members can be maternally inherited (Funkhouser & Bordenstein, ; Goodrich et al., ; Yuan et al., ) or can be actively shaped by the interaction of environment and host genotype (Bolnick, Snowberg, Caporaso et al., ; Bolnick, Snowberg, Hirsch et al., ). Among the extrinsic factors, comparative analyses and perturbation experiments have suggested that diet and habitat heterogeneity are major environmental drivers contributing to gut microbial variation within and between species (Amato et al., ; Barelli et al., ; Bolnick, Snowberg, Hirsch et al., ; Clayton et al., ; Gomez et al., ; Wang et al., ).…”
Section: Introductionmentioning
confidence: 99%